Fischer Type Log-Majorization of Singular Values on Partitioned Positive Semidefinite Matrices - Benju Wang; Yun Zhang (Journal of Function Spaces)
In this paper, we establish a Fischer type log-majorization of singular values on partitioned positive semidefinite matrices, which generalizes the classical Fischer's inequality. Meanwhile, some related and new inequalities are also obtained.